2013
DOI: 10.1055/s-0033-1349356
|View full text |Cite
|
Sign up to set email alerts
|

Radiologic Measurement of Submandibular Gland Ptosis

Abstract: A linear relationship exists between patient age and submandibular gland ptosis, as measured by the distance of the gland from the inferior border of the mandible. To our knowledge, this is the first quantification of the rate and extent of submandibular gland ptosis. A novel grading system for submandibular gland ptosis has been proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…SMG ptosis is an age-related phenomenon in which inferior displacement of both submandibular glands results from laxity of the platysma muscle and skin and can be a concern in cosmetic neck rejuvenation. 9 Ptotic SMGs are symmetrically inferiorly displaced within the submandibular space and are not translated anteriorly into the submental space as is the case with a unilaterally transferred SMG. 9 The asymmetric appearance of a transferred SMG and the history of a prior operation distinguish it from ptotic SMGs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SMG ptosis is an age-related phenomenon in which inferior displacement of both submandibular glands results from laxity of the platysma muscle and skin and can be a concern in cosmetic neck rejuvenation. 9 Ptotic SMGs are symmetrically inferiorly displaced within the submandibular space and are not translated anteriorly into the submental space as is the case with a unilaterally transferred SMG. 9 The asymmetric appearance of a transferred SMG and the history of a prior operation distinguish it from ptotic SMGs.…”
Section: Discussionmentioning
confidence: 99%
“…9 Ptotic SMGs are symmetrically inferiorly displaced within the submandibular space and are not translated anteriorly into the submental space as is the case with a unilaterally transferred SMG. 9 The asymmetric appearance of a transferred SMG and the history of a prior operation distinguish it from ptotic SMGs. Enhancement of the transferred SMG relative to the contralateral SMG appears to depend on the timing of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the distance of the submandibular gland from the inferior border of the mandible is variable. In a study performed by Lee et al [ 6 ], 92.6% of patients older than 65 years of age demonstrated submandibular gland ptosis of 25 mm or more away from the inferior border of the mandible. In addition, numerous younger subjects in Lee's study demonstrated a distance of 20 mm or more between the submandibular gland and the inferior border of the mandible.…”
Section: Discussionmentioning
confidence: 99%
“…In certain patients, ptosis of the submandibular gland is commonly observed, resulting in visible deformation of the submental region. Treatment options for this condition include partial resection, mandibular duplication sutures, and transcervical suspension sutures [43][44][45][46][47][48][49][50][51][52] (Figure 3). However, it is important to note that surgical manipulations on the submandibular gland carry risks such as hematoma formation from glandular vessels, potential damage to the marginal mandibular branch of the facial nerve, and long-term healing complications of salivary gland fistulas.…”
Section: Mixed Platysmaplastymentioning
confidence: 99%